Self-propelled screen-printable catalytic swimmers1. Issue 96 (17th October 2015) - Kumar, Rajan; Kiristi, Melek; Soto, Fernando; Li, Jinxing; Singh, Virendra V.; Wang, Joseph
<x xml:space="preserve">Abstract</x> A highly versatile 2D screen-printing fabrication of nature-inspired fish swimmers is described.